Zina dan Norma Sosial dalam Kitab Fathul Qorib pada Mata Pelajaran Kitab di Pondok Pesantren Raudlatul Muhibbin Al Mustainiyyah Surakarta - Aulia Mursyida; Annisa Nur Rahmah; Adisya Alfatihah; Dilvi Rinta Awanis; Difa Gamar Azizah (Jurnal Ilmu Agama Indonesia, 2025)
This study examines the relationship between the concept of adultery and social norms as described in the book Fathul Qorib in the subject of religious studies at the Raudlatul Muhibbin Al-Mustainiyyah Islamic boarding school in Surakarta. The background of this study is the concern that the substance of classical teachings is not always contextualized with modern social conditions, so that the understanding of adultery norms in Islamic boarding school communities can be distorted or inconsistent. The objectives of this research are: (1) to interpret the teachings on adultery in Fathul Qorib, (2) to identify the social norms that are formed or maintained through these teachings, and (3) to analyze the compatibility or conflict between the teachings of the book and the social practices of the santri. The research method is qualitative with a textual hermeneutic and educational ethnographic approach. Data were obtained through text study of the book, in-depth interviews with teachers and students, and observation of classes. The results show that the teachings of Fathul Qorib emphasize the prohibition of activities that “approach adultery” (taqrîb) and moral sanctions against violators, which in social practice in Islamic boarding schools results in internal disciplinary norms (reporting, reprimands, guidance). However, there is a gap between the formal norms of the book and the reality of social interactions among students (ikhtilât, non-mahram social relationships). This study concludes that teaching the book can strengthen the social norms of the pesantren, but a responsive pedagogical strategy is needed to prevent distortion of norms or hypocrisy among students. Practical suggestions: teachers of religious texts should engage in critical and reflective dialogue with students and align the teaching of religious texts with contextual character building.